Incidencia del medio de comunicación radial parís 103.9 fm en la cultura política juvenil, en jóvenes de 18 a 29 años, en la ciudadela Los Mirtos, del cantón Vinces, en el año 2018 - Elizalde Alvarado, Gilda Zuleyka (2019)
Radio Paris 103.9 FM of the city of Vinces has a regional reach in the provinces of Bolívar, Los Ríos, Guayas and Manabí, locally it has a high level of harmony in the youth population of 18 to 29 years. The youth political culture has a deficiency in the canton Vinces and is that it is not widespread at the cantonal level in the radio communication media, for which it uses types of research such as exploratory and descriptive, having primary information as sources of information and secondary, the sample indicates that 141 young people should be surveyed.,,,,